الإعلال في كتاب الصلاة من سنن أبي داود : دراسة صرفية تحليلية - Nurul Syazwani binti Nor Azizi (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research seeks to clarify different provisions of the phenomena of Al-I'lal in the Arabic verbs that appeared in the Book of Prayer from Sunan Abi Dawood, in order to help the Arabic language learners who study the Prophet's Hadiths on aspects of the roots of Arabic verbs; unaugmented or augmented, the types of verbs, the formation of each verb in all their conjugations and its changes either transformation form, or vowel-less or exchanging form, or deleting form. This is because there are some verbs similar in formulas and words but different in their origins and meanings. The researcher used the descriptive and analytical approach, describing the information about the verbs, their types and structures, and then focused on the rules of Al-I'lal in the Arabic language. Furthermore, this information was analyzed in the verbs that appeared in the Book of Prayer from Sunan Abi Dawood, which includes 769 Hadith, and 258 sections. This research revealed that the verbs that were analyzed in the Book of Prayer were in the total of 184 verbs, deleted forms were 80 verbs, the transformation forms were77 verbs, and the last vowel-less or exchanging forms were 47 verbs. The researcher concluded that the issues of Al-I'lal in the Arabic word should not be underestimated because it is closely related to the Arabic language in that the word formulations came in accordance with their meanings within the sentence.